Driving and Dissipation of Solar-Wind Turbulence: What is the Evidence? - Smith, Charles W.; Vasquez, Bernard J. (Frontiers in Astronomy and Space Sciences, 2021)
Fifty years of solar wind observations have provided extensive data that drives an evolving view of the fundamental nature and dynamics of the magnetic, velocity, and density fluctuations that are ubiquitous throughout the heliosphere. Despite the ongoing examination of ever improving data, fundamental questions remain unanswered because there are very few multi-point measurements from a sufficient number of spacecraft in close proximity to fully resolve the three-dimensional dynamics that are at the heart of the problem. Simulations provide new insights and new questions, but most simulations sacrifice one aspect of plasma physics in order to address another. Computers and computational methods remain insufficient to simulate fully compressive, fully nonlinear, collisionless plasma dynamics with sufficient spatial range and dimension to be considered a complete description of solar wind turbulence. For these reasons, there remain multiple divergent opinions as to the underlying dynamics of solar wind turbulence, dissipation, and the observed heating of the thermal plasma. We review observations of solar wind turbulence in so far as they contribute to an understanding of solar wind heating through the existence of energy reservoirs, the dynamics that move energy from the reservoirs to the dissipation scales, and the conversion into heat of energy associated with coherent fluctuations.